1985
DOI: 10.1902/jop.1985.56.8.492
|View full text |Cite
|
Sign up to set email alerts
|

The Laser Gingivectomy: The Use of the CO2 Laser for the Removal of Phenytoin Hyperplasia

Abstract: A new technique for the removal of phenytoin hyperplasia using the carbon dioxide (CO2) surgical laser is presented as well as a review of laser physics and the current uses of the CO2 laser in dentistry. Twelve cases of phenytoin hyperplasia removed surgically by the CO2 laser are presented; hence a laser gingivectomy. Advantages of the procedure include lack of hemorrhage yielding a dry field, noncontact surgery, sterilization of the surgical area, prompt healing, minimal post operative discomfort, and minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(65 citation statements)
references
References 3 publications
0
64
0
1
Order By: Relevance
“…The excellent hemostasis and absence of postoperative swelling was attributed to increased platelet activation by lasers 15 and sealing of lymphatic vessels. 16 There was no need to sutures, as there is complete hemostasis and improved wound healing. In addition, the laser's sterilization of the surgical wound reduces the need for postoperative care and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent hemostasis and absence of postoperative swelling was attributed to increased platelet activation by lasers 15 and sealing of lymphatic vessels. 16 There was no need to sutures, as there is complete hemostasis and improved wound healing. In addition, the laser's sterilization of the surgical wound reduces the need for postoperative care and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no complications occurred, and this was due to careful pre-operative care, to the use of appropriate surgical technique, and to a controlled postoperative period. 8,10,12,13,18,19,[24][25][26][27][28][29][30] Despite the large number of publications, there is still controversy among clinicians regarding the application of dental lasers to the treatment of periodontal conditions. There is a considerable conflict in results for both laboratory studies and clinical trials, even when using the same laser wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…8,[19][20][21][22][23] Despite several reports on the effects of CO2 surgery on soft tissues, none have used numeric parameters to assess the results of the procedure. 8,10,12,13,18,19,[24][25][26][27][28][29][30] The present study aimed to assess, numerically and statistically, the effect of the use of the CO2 laser on the treatment of gingival hyperplasia in orthodontic patients wearing fixed appliances.…”
Section: Introductionmentioning
confidence: 99%
“…Diode lasers specifically, operate at a wavelength that is easily absorbed by the gingival tissues, while posing little risk of damaging the tooth structure. [25] Pick RM et al presented a 12 cases of phenytoin hyperplasia removed surgically by the CO2 lasers and hence laser gin-givectomy and suggested that in the future the laser may offer an alternative or an advancement to current procedures now used in dentistry (Pick et al 1985) b) Crown Lengthening: Lasers have been promoted for clinical crown lengthening without gingival flap reflection for both esthetic and prosthetic reasons. However, currently there are no controlled longitudinal or cohort studies supporting the use of lasers for clinical crown lengthening using the closed-flap technique.…”
Section: Applications In Periodonticsmentioning
confidence: 99%